IS THERE A CONTINENTAL BIAS IN TRADE? - Salvador Gil-Pareja; Rafael Llorca; José A. Martínez-Serrano (European Regional Science Association (ERSA), 2010)
The relationship between geography and trade is a central topic in international economics. This paper investigates the potential existence of a continental bias in world trade flows on a sample of 182 countries over the period 1990-2006. Using traditional estimation techniques and recent developments in the econometric analysis of the gravity equation, we find robust evidence of an economically significant continental bias in trade. It implies that, other things equal, countries located on the same continent trade more with each other than countries located on different continents. A continent-by-continent analysis reveals that Oceania, America, Europe and Asia are behind this result. Africa is the only region for which the results are not conclusive.
Keywords: F14; 330; Continental bias; gravity equation; intercontinental and intra-continental trade costs